Quorum sensing regulates heteroresistance in Pseudomonas aeruginosa - Lu, Yang; Liu, Yuyang; Zhou, Chenxu; Liu, Yaqin; Long, Yifei; Lin, Dongling; Xiong, Rui; Xiao, Qian; Huang, Bin; Chen, Cha (Frontiers in Microbiology, 2022)
The prevalence and genetic mechanism of antibiotic heteroresistance (HR) have attracted significant research attention recently. However, non- genetic mechanism of HR has not been adequately explored. The present study aimed to evaluate the role of quorum sensing (QS), an important mechanism of behavioral coordination in different subpopulations and consequent heteroresistance. First, the prevalence of HR to 7 antibiotics was investigated in 170 clinical isolates of P. aeruginosa using population analysis profiles. The results showed that P. aeruginosa was significantly heteroresistant to meropenem (MEM), amikacin (AMK), ciprofloxacin (CIP), and ceftazidime (CAZ). The observed HR was correlated with down-regulation of QS associated genes lasI and rhlI. Further, loss-of-function analysis results showed that reduced expression of lasI and rhlI enhanced HR of P. aeruginosa to MEM, AMK, CIP, and CAZ. Conversely, overexpression of these genes or treatment with 3-oxo-C12-HSL/C4-HSL lowered HR of P. aeruginosa to the four antibiotics. Additionally, although downregulation of oprD and upregulation of efflux-associated genes was evident in heteroresistant subpopulations, their expression was not regulated by lasI and rhlI. Moreover, fitness cost measurements disclosed higher growth rates of PAO1ΔlasI and PAO1ΔrhlI in the presence of sub-MIC antibiotic as compared with that of wild-type PAO1. Our data suggest that under temporary antibiotic pressure, downregulation of QS might result in less fitness cost and promote HR of P. aeruginosa.